p21/WAF1 expression as related to p53, cell proliferation and prognosis in epithelial ovarian cancer - Anttila, M A (Nature Publishing Group, 1999)
The role and prognostic value of the tumour suppressor p21/WAF1 expression in epithelial ovarian cancer has not yet been defined. Therefore, the expression of p21/WAF1 was assessed immunohistochemically (IHC) in 316 epithelial ovarian malignancies in relation to p53, cell proliferation and patient survival. p21/WAF1 expression was inversely correlated with p53 and cell proliferation. Low p21/WAF1 expression was significantly associated with high grade of the tumour (P = 0.0005), advanced FIGO stage (P = 0.001) and primary residual tumour (P = 0.0001). Low p21/WAF1 expression was a marker of poor overall survival (P = 0.012). Similarly, p53-positivity and high cell proliferative activity were significant predictors of poor survival in univariate analyses. Moreover, the patients with p21–/p53+ tumours had a poorer overall (P < 0.00005) and recurrence-free (P = 0.0005) survival in univariate analyses, and the p21/p53 expression independently predicted tumour recurrence in Cox's multivariate analysis. Our results suggest that p21/WAF1 expression is mostly p53-dependent in epithelial ovarian cancer. High p21/WAF1 expression seems to function as a negative cell cycle regulator and as a marker of favourable disease outcome in epithelial ovarian cancer. In addition, the patients with their tumour expressing no or low p21/WAF1 protein but positive for p53 had a notably higher risk of recurrent disease, implicating that these patients might be more prone to treatment failures. © 1999 Cancer Research Campaign